ANALISIS PENGUKURAN GEOMETRIS BENDING FOR SUPER HEATER TUBE PADA BOILER DALAM RANGKA CONTINUAL IMPROVEMENT - Johannes Herry Dwijosusanto Serek (Prodi Teknik Industri S1 Institut Teknologi Nasional Malang, 2014)
The term of quality has a meaning as factors obtained from the thing that causes. One mention above in accord with the goal having the arm or the one that is needed. Therefor, the goods must have the certain quality and optimal economic product which is produced to fulfill the customer need. The quality not only related to product which is produced to fulfill the customer need. The quality not only related to product and service but also work operation, machine operator and the system, procedure that are applied including human being attitude aspects.The finding shows that five kind boiler have been obtained that those are not the same in terms of measurement toward boiler pipe involved : Outer diameter, inner diameter and Thickness when the bending test has done before and after the process that are : Boiler 20 ton post-A (before process): outer and inner tolerance diameter 4,5%. Thickness tolerance 7,6%. Boiler 20 ton post-A (after process): outer and inner diameter tolerance 4,8%. 2. Thickness tolerance 17,5%.For the tasted sample by using control chart X-Bar and R how for deviation measurement before and after the process toward outer and inner diameter and also the thickness. Therefor, determining upper control limit, lower control limit, control limit for X-Bar and for range.The computation result and description of control mapping X-Bar and R are clear that in this case there is no data that deviate from the control limit. It can be concluded that production process run well by control. Therefor, based on ISO 9001 : 2000, quality management improvement is focused on process improvement aspect (Continual Improvement) by using quality data that are collected including statistic technique.